KEANEKARAGAMAN JENIS PAKU-PAKUAN DI KAWASAN IUPHHK-HTI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Khamalia, Imban (JURNAL HUTAN LESTARI, 2018)
The study aims to know the diversity of species nails in an secondary forest in regional IUPHHK-HTI PT. Bhatara Alam Lestari to Kabupaten Mempawah. The research is all sports of crops spike in research area. The study was conducted using a method of survey and the sample collection technique in do with or placement tenement sample in doing intentional. The size of tenement her observation is 20 X 20 m, section of the test the as much as to 2% (3,98 Ha) of the area in the ( 199,33 Ha) so there will a 10 tenement observation. the results of the study showed that kind of a nill cecerean INP the highest number with value of having the value of the (52,76), while value INP the lowest on the type of nails remiding worth INP (8,19), index value dominance (C) suggests that dominance not focused on a species in a row, but spread in between all tenement. So the index domination showed that the plants a spike on tenement observation not dominant, because it is still under the standard dominance (<1), and index value diversity (H) highest is spikes cecerean. To grow in a good in plants a nail is caused by temperatures and humidity of the air that shall and get a sunburn enough.Keywords: a nail cecerean, a nail nest of a bird, an terrestrial, Epiphyte, The diversity of specie.